Influence of copper on Gamma-Alpha transformation in gray and nodular cast iron-temperability - Villacorta Arévalo, Héctor (2011)
This research refers to the grey iron lamellar graphite casting and nodular cast iron casting. Both contain variable percentages of copper to a maximum of 4%, cooled in sand molds in which the apparent solubility of copper is limited, to obtain wear-resistant castings, improving the hardenability of gray cast iron and nodular cast iron by the effect of stabilizing the austenite.